BUILDING PRINCIPAL LEADERSHIP ORIENTED TO IMPROVING STUDENT LEARNING OUTCOMES - Farid Haluti; Hasrat A. Aimang; Bernadette O. Gallardo (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2024)
This study aims to identify and develop a principal leadership model oriented towards improving student learning outcomes at SDN Pembina Luwuk. The main problem raised was the low student learning outcomes caused by the less than optimal role of the principal in building a conducive and collaborative learning environment. This research approach used descriptive qualitative methods with data collection techniques through in-depth interviews, participatory observation, and document analysis. Respondents included principals, teachers, students and school committees. The results showed that effective principal leadership is characterized by open communication, participatory decision making, and strengthening achievement-based school culture. In addition, supervision and teacher professional development programs are consistently the main supporting factors in improving teaching quality. The implication of these findings is the need for structured and continuous leadership training for principals, as well as increased involvement of all stakeholders in supporting the teaching-learning process. This research is expected to make a significant contribution to the development of an educational leadership model that is oriented towards student learning outcomes.